7+3(3-2x)=7x+3(3x-2)

Simple and best practice solution for 7+3(3-2x)=7x+3(3x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3(3-2x)=7x+3(3x-2) equation:


Simplifying
7 + 3(3 + -2x) = 7x + 3(3x + -2)
7 + (3 * 3 + -2x * 3) = 7x + 3(3x + -2)
7 + (9 + -6x) = 7x + 3(3x + -2)

Combine like terms: 7 + 9 = 16
16 + -6x = 7x + 3(3x + -2)

Reorder the terms:
16 + -6x = 7x + 3(-2 + 3x)
16 + -6x = 7x + (-2 * 3 + 3x * 3)
16 + -6x = 7x + (-6 + 9x)

Reorder the terms:
16 + -6x = -6 + 7x + 9x

Combine like terms: 7x + 9x = 16x
16 + -6x = -6 + 16x

Solving
16 + -6x = -6 + 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
16 + -6x + -16x = -6 + 16x + -16x

Combine like terms: -6x + -16x = -22x
16 + -22x = -6 + 16x + -16x

Combine like terms: 16x + -16x = 0
16 + -22x = -6 + 0
16 + -22x = -6

Add '-16' to each side of the equation.
16 + -16 + -22x = -6 + -16

Combine like terms: 16 + -16 = 0
0 + -22x = -6 + -16
-22x = -6 + -16

Combine like terms: -6 + -16 = -22
-22x = -22

Divide each side by '-22'.
x = 1

Simplifying
x = 1

See similar equations:

| 12=a-(-18) | | y^3+2y^2=0 | | -(7xy-10)+3(6xy+4)= | | -9/2(x+1)=3 | | 5x+3x^2-2x^3=0 | | 3=n-(-6) | | 0.5b+4=2+3d-0.5 | | 2(-8x+5)+5x=7(x+4) | | -6x+3(3x+12)=18 | | v+(-6)=-24 | | 3x-16+3x=2+6x-18 | | .07x+.05(x-2400)=196 | | -6y-4=-5y-7 | | 2x+3(x-1)=4x-17+2x | | 12t=9(t-15) | | 10.60+106= | | r^4=1024 | | 4u^2+4u-32= | | 9=r(r-8) | | 10.60-106= | | 7-(3n-3)=2-4n | | 2(x+2)+4x=x+5 | | 7r^2-10=25 | | 7x+8=x^2 | | 9(y+9)=8y-7 | | 6b^2-11b-35=0 | | -(b+1)=10-b | | 6a+3=-3(2a-1) | | 4x-10-6x+3=5-9x-7+2x | | 1500+8x=1500+12x | | 106-21.20= | | 6p=3(t+4)-t |

Equations solver categories